South Sudan: The road from the Paris Declaration to the reality of Juba, 2005 - 11 - Greg Larson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
During Sudan's interim period from the end of civil war in January 2005 until South Sudan's independence in July 2011, foreign development agencies provided extensive support and billions of dollars in aid - for which institutional development and capacity building of the nascent Government of Southern Sudan were core priorities. This six-year period thus provides a major case study in modern-day state-building. As a framework for analysis, the paper utilizes the Paris Declaration on Aid Effectiveness - which was signed in February 2005, shortly after Sudan's peace agreement. Assessment of how the Paris principles were utilized in Southern Sudan underscores the limits of the prevailing orthodox approach to development, particularly in fragile post-conflict environments. In such complex, highly challenging contexts, orthodoxy often fails.
Keywords: H11; K00; O19; O20; 330; aid effectiveness; state-building; fragile states; donors; South Sudan